Evaluation of rat occurrence in oil palm plantations using GIS and remote sensing techniques - Chong, Chee Wey (2012)
Rat damage in oil palm plantation brings significant economic losses. In this study, factors that influence rat occurrence were investigated using live trapping and GIS-based multicriteria analysis. 255 rats, mostly Rattus rattus diardii were captured using live trapping from nearly two thousands trap-night efforts. In oil palm plantation, rat species captured is R. r. diardii, R. argentiventer, Maxomys whiteheadi. In forest, rat species captured is R. r. diardii, M. whiteheadi, and M. surifer. Rat capture data was examined using several spatial factors. Factors that influence rat occurrence are found to be palm age, distance from road, distance from mill, and Normalized Difference Vegetation Index (NDVI) value. Binomial and multinomial logistic regression models were developed for prediction of rat occurrence In oil palm plantation. This study identified high, medium, and low rat occurrence area in oil palm plantation; highest rat occurrence (25.35% success rate, 95.31 % points with rat) was recorded in replanting area. Identification of high rat occurrence area allow effective placement of barn owl nest box, for addressing rat problems in resource saving and environmental friendly way.